Correlation Between Degrees of Kyphotic, Procalcitonin, LED, NLR, and PLR with Neurological Deficits and Pain in TB Spondylitis Patients at Adam Malik National Hospital - Yovi Eko Azhra; Ridha Dharmajaya; Muhammad Deni Nasution (Universitas Muhammadiyah Palu, 2024)
Background: Infection by Mycobacterium tuberculosis (TB) affecting the vertebrae is commonly known medically as tuberculous spondylitis. As part of the spectrum of extrapulmonary TB pathology, the impact of such an infection can significantly disrupt an individual's quality of life. Kyphotic deformity, theoretically capable of inducing neurological deficits and chronic pain, is an aspect of this condition that is anticipated to be predictable based on basic diagnostic examinations. This study aims to evaluate the relationship between the degree of kyphosis and laboratory findings such as procalcitonin, erythrocyte sedimentation rate (ESR), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) concerning the level of neurological deficit and pain. Method: This analytical-observational study adopts a cross-sectional design involving a group of patients experiencing TB spondylitis at the Haji Adam Malik General Hospital (HAM GH), Medan, Indonesia. The researchers will evaluate the correlational aspects between independent variables (degree of kyphosis, procalcitonin, ESR, NLR, and PLR) concerning the level of neurological deficit and pain, respectively measured using the American Spinal Injury Association (ASIA) method and visual analog scale (VAS). Results: Among the 39 patients included, with an average age of 37.44 ± 16.09 years, a significant correlation (P<0.05) was found between the five independent variables and the patients' neurological deficit, with respective correlation coefficients of 0.877; -0.523; -0.568; 0.564; and 0.374. However, only the degree of kyphosis, procalcitonin, and ESR showed a significant correlation with pain, with correlation coefficients of 0.530; 0.543; and 0.690, respectively, which was not observed in the NLR/PLR analysis (P>0.05). Conclusion: The degree of kyphosis, procalcitonin, and ESR are correlated with both neurological deficits and pain scales, whereas NLR/PLR is only associated with the degree of neurological deficit in patients.